Real time EPG recordings of tomatopotato psyllid (Bactericera cockerelli) feeding on tomato - Sandanayaka, W.R.M.; Page-Weir, N.E.M.; Fereres, A. (New Zealand Plant Protection, 2011)
The stylet penetration behaviour of tomatopotato psyllid (TPP; Bactericera cockerelli Hemiptera Psyllidae) a phloem feeder was monitored using an electrical penetration graph (EPGDC system) technique Fifteen adult psyllids were randomly selected from a colony and monitored for 8 h on tomato plants under laboratory conditions EPG waveforms generated during stylet penetration into the plant tissues were categorised based on amplitude frequency voltage level and electrical origin The main waveforms representing salivary sheath secretion and other stylet pathway activities (C) first contact with phloem (D) salivation in phloem sieve tubes (E1) and phloem sap ingestion (E2) were similar to the Asian citrus psyllid Diaphorina citri and this was confirmed by histological studies Phloem ingestion was seen from 12 out of 15 psyllids tested The time to first contact of phloem from the beginning of recording was 1163 h and the total duration of phloem ingestion recorded was from 1 min to 52 h within the 8 h recording period The information gathered on the feeding behaviour of TPP from this study will be applicable for future studies to understand the transmission of Candidatus Liberibacter solanacearum by TPP as well as other Liberibacter and TPP management studies